Evaluation of the nitric oxide radical scavenging activity of manganese complexes of curcumin and its derivative - Yaowared Sumanont (2018)
Curcumin manganese complex (CpCpx) and diacetylcurcumin manganese complex (AcylCpCpx) were determined as to their effect on the nitric oxide (NO) radical scavenging in vitro method using a sodium nitroprusside generating NO system compared with their parent compound and astaxanthin, an extreme antioxidant. All compounds effectively reduced the generation of NO radicals in a dose dependent manner. They exhibited strong NO radical scavenging activity with low IC 50 values. The IC 50 values of curcumin, diacetylcurcumin, CpCpx and AcylCpCpx obtained are 20.39±4.10 μM, 28.76±1.48 μM, 9.79±1.50 μM and 8.09±0.99 μM, respectively. CpCpx and AcylCpCpx show greater NO radical scavenging than their parent compounds, curcumin and acetylcurcumin, respectively. However, the IC 50 values of curcumin and related compounds were found to be less than astaxanthin, an extreme antioxidant, with the lower IC 50 value of 3.42±0.50 μM. © 2004 Pharmaceutical Society of Japan.